Multiple ways of belonging in a multicultural city - Sujoldžić, Anita (Array, 2009)
Abstract: The focus of the present study is on the interdependence of language and urban identity set within the framework of theory of practice and the concept of the right to the city. It is concerned with the formation of local identities in the context of a multicultural city of Pula, in the Croatian region of Istria, characterized by a substantial presence of immigrant and ethnic minority groups. The paper explores to what extent the image of the city, with its spatial and social structure, as well as socio-economic and historic context determines discourse on multicultural interactions as well as the ways those images shape a sense of identity, and how these identities are affected by interpersonal and inter-group communication. By looking into factors and processes through which different dimensions of identity become salient, specific attention is given to how power relations influence the dynamics of identity negotiation and the re/articulation of potential hierarchy of differences